Behavior of Montandoniola confusa Streito & Matocq (Hemiptera: Anthocoridae) preying upon gall-forming thrips Gynaikothrips ficorum Marchal (Thysanoptera: Phlaeothripidae) - Tavares, Adauto M.; Torres, Jorge B.; Silva-Torres, Christian S. A.; Vacari, Alessandra M. [UNESP] (Elsevier B.V., 2013)
The gall-forming thrips Gynaikothrips ficorum Marchal (Thysanoptera: Phlaeothripidae) is recorded in all regions where its host plant, Ficus microcarpa (Marchal) (Moraceae), has been cultivated as an urban and interior landscape plant species, including potted plants and bonsai. Similarly, the thrips predator Montandoniola confusa Streito & Matocq (Hemiptera: Anthocoridae) has generally followed the prey distribution. The gall induced by thrips degrades the plant foliage, and the thrips themselves can be annoying for people both outdoors and indoors. The galls, however, create a microcosm with all developmental stages of the thrips and its predator. In this study we present the first records of M. confusa in South America, document the species' widespread concomitant occurrence across Brazil, and report our studies of three aspects of M. confusa predation upon the eggs, larvae/prepupae, and adults of G. ficorum thrips: (i) functional response of the predator adult female as a function of different densities of thrips eggs, larvae/prepupae and adults separately: (ii) predation on eggs by adult M. confusa with adult thrips present in the gall; and (iii) adult M. confusa prey preferences when all thrips stages occurred simultaneously in the gall. For all three thrips life stages tested, the predator exhibited a type II functional response. Despite the availability of different life stages in the gall, M. confusa adults are capable of preying upon all life stages of G. ficorum, predation was preferentially on thrips eggs, with an estimated similar to 10-fold greater predation on eggs compared to larvae/prepupae and adult thrips. Egg predation was unaffected by the presence of defensive adult thrips in the gall under low densities (<30 eggs/gall) but when egg densities were greater than 30 eggs/gall, it was reduced when adult thrips were present. However, the relative number of thrips adults per gall did not statistically change the outcome. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Predation; functional response; Prey defense; Prey preference